Explicit and Implicit Vocabulary Instruction in the Algerian EFL Context - BENYAHIA, Amel (Journal of Human Sciences, 2020)
This study investigates explicit and implicit methods of vocabulary instruction in an Algerian EFL context; namely L’ENS ‘Assia Djebar’ of Constantine. Tools of data collection consist of an analysis of course curricula, in addition to a questionnaire administered to 14 teachers of English at the English department at l’ENSC. Results of the investigation reveal that vocabulary instruction follows both explicit and implicit approaches. The analysis of subject programs showed that vocabulary is implicitly involved in most subjects. Most analysed programs do not bear a direct relevance to vocabulary except for ‘Reading Techniques’ and TEFL (Teaching English as a Foreign Language) modules where vocabulary is overtly involved. In addition, teachers’ answers to the questionnaire show that most of them follow both approaches to introduce their learners to new vocabulary. Whereas the explicit approach is manifested through the introduction of new vocabulary and the explanation and consolidation of their meaning through practice inside the classroom; the implicit method is implemented through extensive reading assignments which contribute to a large extent in extending learners’ vocabulary store as a by product of getting further information about the subject matter.